2019
DOI: 10.26577/ijbch-2019-1-i24
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of copolymer based on poly (vinyl alcohol) and 2-ethylhexyl acrylate as admixture for cement pastes

Abstract: In this study, three composition ratios of [polyvinyl alcohol (PVA)-2-ethylhexyl acrylate (2-EHA)] were prepared by grafting polymerization techniques in aqueous solution using ammonium persulfate as free radical initiator. The ratio of PVA/2-EHA in the grafted copolymers was variable: 1/ 8, 1/ 6 and 1/ 4, respectively. The obtained grafted copolymers were characterized by different techniques including FTIR, 1 H NMR, TGA and DSC. The copolymers were mixed with cement to study the physicomechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The grafting polymerization in presence of APS, including the initiation, propagation, and termination steps, is shown in Scheme 1. The preparation of the copolymers and the method of analysis (FTIR, 1 H NMR, DSC, and TGA) follow those reported by Negim et al (2019).…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…The grafting polymerization in presence of APS, including the initiation, propagation, and termination steps, is shown in Scheme 1. The preparation of the copolymers and the method of analysis (FTIR, 1 H NMR, DSC, and TGA) follow those reported by Negim et al (2019).…”
Section: Methodsmentioning
confidence: 89%
“…The properties of the obtained grafted copolymers and the physical and mechanical properties of the pastes mixed with copolymers have been investigated by Negim et al (2019). It was observed that the thermal stability and transition glass temperature (Tg)of the copolymers are directly proportional to the amount of 2-EHA and that the copolymers are miscible because only one Tg was found.…”
Section: Structure Of Copolymersmentioning
confidence: 99%
See 2 more Smart Citations